Pengaruh Kualitas Pelayanan dan Kepercayaan terhadap Kepuasan Anggota pada Kopel Bulog Pusat di Jakarta Selatan - Desia Pratiwi (Jurnal Publikasi Ilmu Manajemen, 2025)
Service quality is an action that reflects the level of strength and excellence of the company in measuring how well its service meets the needs, desires, and expectations of a customer. This research discusses the influence of service quality and trust on the satisfaction of members of the at Kopel Bulog Pusat in South Jakarta. Using a quantitative method with data collection techniques such as observation, questionnaires distributed to 92 members as respondents, and literature study methods. This study aims to simultaneously determine whether service quality and trust affect member satisfaction. The hypothesis used is that there is a suspected influence of service quality and trust on the satisfaction of members of Kopel Bulog Pusat. Using the SPSS version 27 analysis tool, the research results indicate that the variables of service quality and trust have a positive and significant effect on member satisfaction at Kopel Bulog Pusat. With an adjusted R Square value of 0.266, which means 26.6% of member satisfaction at Kopel Bulog Pusat is influenced by independent variables, and the remaining factors are not discussed in this study.